Note—Commonality Strategies: Value Drivers and Equivalence with Flexible Capacity and Inventory Substitution - Van Mieghem, Jan A. (Management Science, 2004)
Commonality strategies assemble different products from at least one common component and one other product-specific component. The distinguishing feature of commonality, i.e., the presence of dedicated components to be assembled with a common component, is shown to be mathematically inconsequential in the sense that the unified commonality problem for two products can be reduced to an equivalent substitution flexibility problem without those dedicated components. This significant simplification provides the first general, closed-form condition for commonality adoption and identifies its value drivers. Commonality is optimal even for perfectly correlated demands if products have sufficiently different margins. This introduces the "revenue-maximization option" of commonality as a second benefit that is independent of the traditional risk-pooling benefit. "Pure commonality" strategies are never optimal unless complexity costs are introduced. Dual sourcing, externalities, and operational hedging features of commonality are discussed.